ACESSO MÓVEL ÀS INFORMAÇÕES DE SAÚDE DO PACIENTE UTILIZANDO COMPUTAÇÃO UBÍQUA - Paz, Leandro F.; Weber, Juliano G.; Maran, Vinicius; Machado, Alencar; Boufleur, Rafael (Salão do Conhecimento, 2013)
Resumo